The Influence of Media Narratives and Ombudsman Statements on Public Understanding of School Entrance Selection in the Riau Islands - Kremer, Hendri; Ramli, Arwin; Mambarasi Nehe, Berita; Safitri, Ria; Lestari Harahap, Widya (EDUCATION JOURNAL OF INDONESIA, 2025)
This study examines the influence of media narratives and Ombudsman statements on public understanding of the New Student Admissions System (SPMB) process in the Riau Islands Province. Amidst challenges to transparency in educational selection, the role of the media and oversight institutions such as the Ombudsman is crucial in shaping public opinion. This study uses a Systematic Literature Review (SLR) approach combined with online news analysis to identify how media narratives frame the issue of educational selection and how the Ombudsman's statements are received by the public. Data were obtained from journal articles, reports from related institutions, and online news covering document verification in the 2025 SPMB selection. The results show that the media plays a significant role in shaping public perception through framing that highlights administrative issues, which can undermine trust in the selection policy. Furthermore, the Ombudsman's role in increasing transparency is essential to correct procedural inconsistencies and increase public trust. Collaboration between the media, the Ombudsman, and the public has proven crucial to creating better understanding and reducing uncertainty related to the selection process. This study recommends strengthening public communication policies at the regional level, particularly in terms of transparency and public participation.